2012
DOI: 10.1136/bmj.e356
|View full text |Cite
|
Sign up to set email alerts
|

25 year trends in first time hospitalisation for acute myocardial infarction, subsequent short and long term mortality, and the prognostic impact of sex and comorbidity: a Danish nationwide cohort study

Abstract: Objectives To examine 25 year trends in first time hospitalisation for acute myocardial infarction in Denmark, subsequent short and long term mortality, and the prognostic impact of sex and comorbidity.Design Nationwide population based cohort study using medical registries. Setting All hospitals in Denmark.Subjects 234 331 patients with a first time hospitalisation for myocardial infarction from 1984 through 2008. Main outcome measuresStandardised incidence rate of myocardial infarction and 30 day and 31-365 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
296
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(336 citation statements)
references
References 48 publications
32
296
1
7
Order By: Relevance
“…A similar pattern was observed in young women with rates of decline of 5% and 38% during the same time periods. This is encouraging, particularly in the context of data from Denmark and the UK showing declining mortality and also a sharp fall in standardised incidence rates for acute myocardial infarction indicating that coronary prevention, as well as acute treatments, has contributed to recent mortality trends (4,5). Meanwhile an Australian study reminds us that myocardial infarction is but one of several manifestations of cardiovascular disease by reporting that decreasing incidence and recurrence rates for hospitalised CHD from 2000 to 2007 have also been seen for cerebrovascular and peripheral arterial disease (6).…”
mentioning
confidence: 93%
“…A similar pattern was observed in young women with rates of decline of 5% and 38% during the same time periods. This is encouraging, particularly in the context of data from Denmark and the UK showing declining mortality and also a sharp fall in standardised incidence rates for acute myocardial infarction indicating that coronary prevention, as well as acute treatments, has contributed to recent mortality trends (4,5). Meanwhile an Australian study reminds us that myocardial infarction is but one of several manifestations of cardiovascular disease by reporting that decreasing incidence and recurrence rates for hospitalised CHD from 2000 to 2007 have also been seen for cerebrovascular and peripheral arterial disease (6).…”
mentioning
confidence: 93%
“…For instance, Thune et al found that antecedent HTN at the time of MI was strongly associated with an increased risk of future heart failure, stroke, cardiovascular death and a composite endpoint consisting of death, myocardial infarction, heart failure, stroke, or cardiac arrest in more than 14.000 patients included in the VALI-ANT trial (Valsartan in Myocardial Infarction Trial) [4]. Nevertheless, over the last years, reperfusion strategies and pharmacological interventions were significantly refined and consequently improved the outcome of patients presenting with acute MI [25]. These advances might have modified the relationship between HTN and the clinical course after STEMI [26].…”
Section: Antecedent Hypertension Baseline Risk Profile and Clinical mentioning
confidence: 99%
“…The incidence of ACS is declining in most developed countries [3,4]. Lifestyle adjustments in the general population, e.g., reduction in smoking and of serum cholesterol levels, have contributed to the reduction in incidence [5].…”
Section: Acute Coronary Syndromementioning
confidence: 99%